Genomic sequencing and analyses of Lymantria xylina multiple nucleopolyhedrovirus. - Nai, Yu Shin; Wu, Chih Yu; Wang, Tai Chuan; Chen, Yun Ru; Lau, Wei Hong; Lo, Chu Fang; Tsai, Meng Feng; Wang, Chung Hsiung (BioMed Central, 2010)
BACKGROUND: Outbreaks of the casuarina moth, Lymantria xylina Swinehoe (Lepidoptera: Lymantriidae), which is a very important forest pest in Taiwan, have occurred every five to 10 years. This moth has expanded its range of host plants to include more than 65 species of broadleaf trees. LyxyMNPV (L. xylina multiple nucleopolyhedrovirus) is highly virulent to the casuarina moth and has been investigated as a possible biopesticide for controlling this moth. LdMNPV-like virus has also been isolated from Lymantria xylina larvae but LyxyMNPV was more virulent than LdMNPV-like virus both in NTU-LY and IPLB-LD-652Y cell lines. To better understand LyxyMNPV, the nucleotide sequence of the LyxyMNPV DNA genome was determined and analysed.